Perbandingan Nilai Pre-Test dan Post-test Praktikum Gross Anatomi Sistem Reproduksi Pria Menggunakan Video Dubbing dan Power Point di PSPD FKIK UNJA Tahun 2013 - Dedy Kurniawan; Nindya Aryanty (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2013)
ABSTRACT Background: Learning gross anatomy might be conducted using variety of methods to increase student knowledge such as through tutorials, lectures and laboratory session. These methods require a media to deliver the learning material. Software power point has been used as a media to deliver gross anatomy material in Medical School of Jambi University on preparation session before laboratory session started. However, these preparation session since 2012/2013 academic year were no longer held. In the other hand, some teachers tried to modified Acland video of gross anatomy by dubbing its english language to indonesia language in order to help students comprehend the material better. Objectives: This study aimed to identify score differences of pre-test and post-test among two students group. The first group was an experimental group where students experiencing preparation session using Acland dubbing video. The other group was control group where student experiencing preparation session using power point. Methods: The design of this experimental study is control group pre-test and post-test. 83 medical students of Jambi University who registered the reproductive system modul were totally sampled and than devided into two groups. Short answer question were arranged as an intrumental test to measure students knowledge before (pre-test) and after (post-test) preparation session. Results: Pre-test score between those two groups are not differ significantly (p = 0.397). Post-test score between those two groups are also not differ significantly (p = 0.157). However, the gain score (an avarage spatial score between post-test dan pre-test) among those two groups are differ significantly (Gain: p = 0.005; N.Gain: p = 0.005) where experimental group is higher than the control group. Conclusion : Post-test score of between experimental group where students experiencing preparation session using Acland dubbing video is not differ significantly to control group where students experiencing preparation session using power point. Since, the preparation session is no longer held, institutions may consider the use of Acland dubbing video to facilitate students constructing prior knowledge before the laboratory session started. Keywords: Gross Anatomy, Dubbing Video, Power point